2018
DOI: 10.1021/acs.cgd.8b00137
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Solid-State Synthesis of High Yield Mixed Halide Perovskites for Easily Tunable Composition and Band Gap

Abstract: We report the preparation of mixed halide hybrid perovskites (CH3NH3PbI3‑x Br x ) using a solvent-less mechanosynthesis route. Compositional analysis using EDXRF microscopy has confirmed the production of the desired materials. As relative abundance of halogen (x) increases, the tetragonal phase gradually transforms to cubic phase and the band gap tunability of the material is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…solvent-less solid-state synthesis) for the design of a wide range of perovskites. [12][13][14][15][16] The combination of the mechanical energy generated under ballmilling conditions and the inherent chemical modification of structures/surfaces make this methodology extremely promising for alternative greener perovskite synthesis. Moreover, ball-milling procedures allow the formation of more stable perovskites, which are not degraded, forming MA 4 PbI 6 •2H 2 O or MA 4 PbI 4 Br 2 •2H 2 O, within a short time, by reaction with ambient humidity.…”
Section: Introductionmentioning
confidence: 99%
“…solvent-less solid-state synthesis) for the design of a wide range of perovskites. [12][13][14][15][16] The combination of the mechanical energy generated under ballmilling conditions and the inherent chemical modification of structures/surfaces make this methodology extremely promising for alternative greener perovskite synthesis. Moreover, ball-milling procedures allow the formation of more stable perovskites, which are not degraded, forming MA 4 PbI 6 •2H 2 O or MA 4 PbI 4 Br 2 •2H 2 O, within a short time, by reaction with ambient humidity.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that a number of recent publications report on the synthesis Cs 2 [AgIn]Cl 6 [9,10], but its bromide analogue has, to the best of our knowledge, not been reported so far. We used a mechanochemical approach that previously been used successfully for the synthesis of lead halide perovskite materials [11][12][13][14][15]. This technique is advantageous for the formation of compounds with narrow existence region [16].…”
Section: Introductionmentioning
confidence: 99%
“…In general, preparation methods of perovskites require energy‐consuming solvothermal conditions using elevated temperatures and pressures for homogeneity of reaction mixtures . Recently, a broad set of alternative synthesis methods of metal halide perovskites involving ultrasound‐assisted,, microwave‐assisted, and mechanochemical approaches has been developed. Among them, the mechanochemical reactions offer a significant advance by avoiding the use of solvent, dramatically shortening synthesis times and providing phase‐pure products.…”
Section: Introductionmentioning
confidence: 99%
“…These initial investigations have opened the door for further discovery and design of novel perovskite materials with optoelectronic quality. Thus, subsequent studies by our group and others have shown that the mechanochemical strategy can be successfully extended for the synthesis of other family of single‐cation lead halide 3D perovskites with the formula of APbX 3 (where A = FA, Cs, GUA; X = Cl, Br, I) in the form of bulk powders or colloidal nanocrystals as well as for the mixed‐cation hybrid (MA) x (FA) 1‐ x PbI 3 and (GUA) x (MA) 1‐ x PbI 3 systems (GUA = guanidinium) . More recently, Kanatzidis and co‐workers utilized the solid‐state grinding method for the synthesis of 2D layered Ruddlesden–Popper (BA) 2 (MA) n ‐1 Pb n I 3n+1 ‐type perovskites .…”
Section: Introductionmentioning
confidence: 99%